Frequency Dictionary of Contemporary Portuguese - Camargo Biderman, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThis article describes the compilation of a frequency dictionary of contemporary Brazilian Portuguese. It discusses some of the problems encountered and the solutions proposed, and introduces some useful tools that the author intends to develop from the dictionary.